Hubungan Pemakaian Kb Suntik 3 Bulan Dengan Pertambahan Berat Badan Di Klinik Pratama Tanjung Delitua Tahun 2024 - Lubis, Rhina Chairani; -, Masni (Jurnal Maternitas Kebidanan, 2024)
The 3-month injectable contraceptive is an injection containing the hormone progesterone, which has a side effect of weight gain. According to data from the World Health Organization (WHO) in 2020, around 842 women using the 3-month injectable contraceptive experienced an average weight increase. This study aims to determine the relationship between the use of the 3-month injectable contraceptive (progestin) and weight gain among family planning acceptors at the Pratama Tanjung Delitua Clinic in 2024. The research design uses a quantitative survey method with a cross-sectional approach. The study was conducted at the Pratama Tanjung Delitua Clinic with a total population of 20 respondents. Data analysis was conducted using univariate and bivariate analyses. The results of the study showed a significant relationship between the use of the 3-month injectable contraceptive and weight gain based on the Chi-Square test, with the following p-values: by age 0.001, by education 0.025, by occupation 0.012, by sources of information 0.038, and by duration of use 0.010 (< 0.05). The conclusion of this study is that there is a significant relationship between the use of the 3-month injectable contraceptive and weight gain. It is recommended that mothers experiencing weight gain follow a low-calorie diet and engage in physical exercise. Keywords: Relationship, 3-Month Contraceptive, Weight Gain